MEDIA KOMUNIKASI TRADISIONAL PADA MASYARAKAT JAWA - Rita Istari (Berkala Arkeologi, 2001)
The Indonesian nation in general and the Javanese in particular have had various abilities as a frame of reference that lasted for generations. Thus the various capabilities that exist today are actually only products of the "local genius" of the past. Javanese people since ancient times have always emphasized the connection between the past, present and future.